GAYA KOMUNIKASI PIMPINAN DALAM MENGEMBANGKAN INOVASI ORGANISASI (Studi Kasus Kepemimpinan Kepala Dinas Kependudukan dan Pencatatan Sipil Kabupaten Padang Pariaman) - Dedy Andhika; Bob Alfiandi; Aidinil Zetra (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This research discussed some communication styles of a leader in developing inovation on Department of Population and Civil Registration of Padang Pariaman District. This research aimed to describe communication styles which are applied by Head of Department as the leader. The theory in this study uses the theory of communication style according to Steward L. Tubbs and Sylvia Moss (1998), namely: the controlling styles, the equalitarian style, the structuring style, the dynamic style, the relinguishing style, and the withdrawal style. Using this descriptive qualitative research method under the constructivist paradigm. The results of the study conclude, Head of Department of Population and civil Regulation of Padang Pariaman District as a leader has applied five styles of of six organization communication styles introduced by Steward L. Tubbs dan Sylvia Moss (1998). They proposed the controlling styles, the equalitarian style, the structuring style, the dynamic style, and the withdrawal style. The application of these communication styles has impacted on the increase of quality achievements of Department of Population and Civil Regulation of Padang Pariaman District within some years of his inovation policy.